Towards an economics methodology: exploring the philosophical foundations of Economics - (:unkn) unknown (International Journal of Research in Education and Applied Sciences, 2015)
Concerned with the contradicting approaches to ethics and economics in business management, the author examines the decision-making patterns of workers and managers of a construction firm. The drive behind the workers (and managers) falls roughly into three categories of incentives. The incentives coincide with the three tendencies in man which define the Plato-Aristotelian psychograph. When the tendencies are in accord with the Aristotelian bonum rationis (good of practical reasonableness), there is synergy in the incentives. The alignment of incentives calls for fundamental behavioral postulates which should underpin ethico-economic systems
Article published in International Journal of Research in Education and Applied Sciences
Concerned with the contradicting approaches to ethics and economics in business management, the author examines the decision-making patterns of workers and managers of a construction firm. The drive behind the workers (and managers) falls roughly into three categories of incentives. The incentives coincide with the three tendencies in man which define the Plato-Aristotelian psychograph. When the tendencies are in accord with the Aristotelian bonum rationis (good of practical reasonableness), there is synergy in the incentives. The alignment of incentives calls for fundamental behavioral postulates which should underpin ethico-economic systems
Keywords: incentives; virtue; economics; profit; ethics; goals; end; factors; synergy; alignment of incentives; common good; practical reason; motivation.